Chest radiographic appearances in adult inpatients admitted with swine flu infection: Local experience in Melbourne. Issue 1 (5th September 2012) - Pirakalathanan, Janu; Lau, Kenneth K; Joosten, Simon A
Abstract Introduction The influenza A virus (H1N1) pandemic began in Mexico in March 2009. As of July 2009, there were 5298 reported cases in Australia including 10 deaths. The aim of this review is to demonstrate the local chest radiographic findings in adult inpatients with proven H1N1, to assess the radiological disease progression and resolution, and to evaluate whether the severity of chest X‐rays findings had a bearing on the length of admission and need for intensive care admission. Methods Eleven H1N1 patients (5 males and 6 females, mean age of 36), presenting with cough (64%), fever (55%) and shortness of breath (55%), were admitted to our hospital between 13 August and 1 November 2010. Details of radiographic features, risk factors, clinical course including length of stay, doubling time of consolidation and time for 50% resolution of consolidation were recorded and analysed. Results Seventy‐three per cent of our patients presented with bilateral mid and/or lower zone alveolar consolidation. One patient with underlying cystic fibrosis had only bilateral upper zone consolidation. No pleural effusion, lymphadenopathy or cardiomegaly was noted on any of the plain chest radiographs. The mean doubling time of consolidation was 1.5 days. The mean time for 50% resolution of consolidation after antiviral treatment was 10.5 days. The average length of stay in hospital was 22 days. Ninety‐one per cent of our patients required intensive‐care unit admission with 50% of those requiring intubation. Conclusion Rapid progression of bilateral mid and lower zone air‐space opacities in relatively young unwell patients, with lack of pleural effusion, pericardial effusion or lymphadenopathy on plain radiographs, should raise the clinical suspicion of H1N1 infection. Patients requiring hospital admission usually show slow clinical and radiological improvement, and require prolonged hospital stays.